An Empirical Study to Investigate the Impact of Social Networking Sites on Student?s Academic Performance and Attitude in Case of Pakistan - HAMEED, Zahid; MAQBOOL, Adnan; ASLAM, Naeem; HASSAN, Ehsan ul; ANWAR, Maqsood (Asian Journal of Empirical Research, 2013)
The purpose of study is to assess the effect of social networking sites on students’ academic performance and student’s behavior. The variables that determine the use of social networking sites as the independent variable and the dependent variables are students’ academic performance and student’s behavior. The population of this research was the university students of twin cities Rawalpindi and Islamabad (Pakistan). The data was collected through questionnaires, and sample size was 300. The data were collected from both public and private universities. The questionnaire contains the four sections. The first section and the second section contains the general questions about the social networking sites, the third part of questionnaire assess students 'academic performance and the last one is used to assess students' behavior. SPSS was used for the analysis of descriptive statistics and in AMOS structural equation modeling was used to test hypotheses of the data. The results of this study shows positive and significant relationship between the social networking sites and students' academic performance and their behavior. Facebook and Twitter are mostly use by the students. The findings of this study are limited because it covers only education sector.